2016
DOI: 10.1007/s11255-016-1492-8
|View full text |Cite
|
Sign up to set email alerts
|

The learning curve for access creation in solo ultrasonography-guided percutaneous nephrolithotomy and the associated skills

Abstract: The increase in experience lead to an improvement in the puncture duration and times, which accompany with better stone-free rates and lower complications. We propose that 60 operations are sufficient to gain competency, and a cutoff point of 120 operations will allow the surgeon to achieve excellence in the solo US-guided PCNL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…The SFR increased with experience and achieved an overall of 75% for all the procedures. Similar findings were reported by Yu et al [47], their study concluded that 60 procedures are necessary for proper USGA PCNL experience, 120 represent excellent performance and nearly perfect results are obtained after 180 procedures.…”
Section: Resultssupporting
confidence: 88%
“…The SFR increased with experience and achieved an overall of 75% for all the procedures. Similar findings were reported by Yu et al [47], their study concluded that 60 procedures are necessary for proper USGA PCNL experience, 120 represent excellent performance and nearly perfect results are obtained after 180 procedures.…”
Section: Resultssupporting
confidence: 88%
“…These changes were within reasonable limits (4.4 to 1.3 min and 2.1 to 1.2 attempts). The increase in the stone-free rate from 68.3% to 93.3% showed a typical learning curve problem [20]. The authors assume that competence and excellence in UPNL is achieved after 60 and 120 operations, respectively.…”
Section: Stone Scores and Learning Curvesmentioning
confidence: 95%
“…Classical publications on FPNL learning curves show that operating room (OR) time-related competence is reached after 60 cases, with acceptable radiation doses after 120 cases. Some recent clinical papers dealt with learning curves for UP [18], FPNL [19], UPNL [20] and FUPNL [21].…”
Section: Stone Scores and Learning Curvesmentioning
confidence: 99%
“…Residual calculi and severe hemorrhage are the two major challenges to implementing tubeless PCNL. Avoiding intraoperative bleeding depends greatly on the experience and skill of the surgeon (18). Therefore, we recommend that tubeless PCNL should only be carried out by experienced surgeons.…”
Section: Skilled and Gentle Operation To Avoid Complicationsmentioning
confidence: 99%